Detoxification of spent cathode carbon blocks from aluminum smelters by joint controlling temperature-vacuum process. (10th March 2020) - Xie, Mingzhuang; Li, Rongbin; Zhao, Hongliang; Liu, Wei; Lu, Tingting; Liu, Fengqin
Abstract: The spent cathode carbon block (SCCB) from aluminum reduction cells is considered to be a hazardous material due to containing a large amount of soluble fluoride salts and toxic cyanides. The serious environment pollution and ecological destruction will be caused by being openpiled or buried of SCCB. A joint temperature-vacuum controlling process for treating SCCB is proposed in this paper. The thermodynamic analysis by FactSage 7.0, series of experimental investigation, and characteristics tests on the product materials by SEM and XRD were carried out. The factors including temperature, vacuum pressure and retention time that influence the SCCB's detoxification effects were comprehensively investigated and discussed in detail. It was found out that the soluble fluoride content can be reduced to a level of 3.5 mg·L −1 while cyanide is completely decomposed. A fixed carbon content of 97.89% in the treated materials is obtained under the optimum temperature and vacuum controlling conditions. Graphical abstract: Image 1 Highlights: Fluoride and carbon can be separated by joint temperature-vacuum controlling process. The interaction between temperature and vacuum in detoxification process is proposed. The fixed carbon content of the residue after treatment was 97.89% with high purity.